2009
DOI: 10.1080/03008200802684623
|View full text |Cite
|
Sign up to set email alerts
|

Dysplastic Histogenesis of Cartilage Growth Plate by Alteration of Sulphation Pathway: A Transgenic Model

Abstract: Mutations in the diastrophic dysplasia sulphate transporter (dtdst) gene causes different forms of chondrodysplasia in the human. The generation of a knock-in mouse strain with a mutation in dtdst gene provides the basis to study developmental dynamics in the epiphyseal growth plate and long bone growth after impairment of the sulphate pathway. Our microscopical and histochemical data demonstrate that dtdst gene impairment deeply affects tissue organization, matrix structure, and cell differentiation in the ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Mutations in hSLC26A2/DTDST cause several related clinical phenotypes of chondrodysplasia (22,35). A related murine phenotype was generated by genetic knock-in of a mutation homologous to a human mutation associated with disease of moderate severity (10,14). The several hSLC26A2 disease mutations that have been subjected to functional study exhibited decreased SO 4 2Ϫ uptake into oocytes (29) or HEK-293 cells (28).…”
Section: Somentioning
confidence: 99%
“…Mutations in hSLC26A2/DTDST cause several related clinical phenotypes of chondrodysplasia (22,35). A related murine phenotype was generated by genetic knock-in of a mutation homologous to a human mutation associated with disease of moderate severity (10,14). The several hSLC26A2 disease mutations that have been subjected to functional study exhibited decreased SO 4 2Ϫ uptake into oocytes (29) or HEK-293 cells (28).…”
Section: Somentioning
confidence: 99%
“…An SLC26A2 chondrodysplasia has been partially phenocopied in the Slc26a2 A386V knock-in mouse, which exhibited post-natal growth retardation, reduced mobility, and 50% mortality by P21 associated with skeletal abnormalities and reduced epiphyseal growth plate thickness. Chondrocyte proliferation and differentiation were delayed, and cultured chondrocytes were nearly devoid of SO 4 2− uptake (Forlino et al, 2005), reflecting in vivo chondrocyte inability to utilize extracellular cysteine as a source of SO 4 2− for macromolecular sulfation (Pecora et al, 2006), and leading to undersulfated proteoglycans of cells and matrix, disorganization of collagen fibers, premature onset of mineralization (Cornaglia et al, 2009) and failure of fibronectin matrix assembly (Galante and Schwarzbauer, 2007). BMP-2 transcriptionally up-regulated SLC26A2 in C3H10T1/2 chondrocytes through interactions with a xenobiotic response element, and binding sites for SP-1 and CFBA1 in the SLC26A2 promoter (Kobayashi et al, 1997).…”
Section: Slc26 Transporters Of Animalsmentioning
confidence: 99%
“…Recent studies in transgenic mice showed that proteoglycans are not only structural components of cartilage architecture, but also play a dynamic role in the regulation of chondrocyte growth and differentiation (13).…”
mentioning
confidence: 99%